Development of articulate storyline learning media integrated with religious values for sexual education in elementary school children - Indriani, Fitri; Aini, Nur (Universitas Ahmad Dahlan, 2023)
The escalating prevalence of violent behavior, sexual deviations, and juvenile delinquency within educational settings underscores the urgency for effective intervention strategies. This study endeavors to address this pressing issue by designing religious, value-oriented, narrative-driven educational media aimed at imparting sexual education to elementary school children. Employing a Research and Development (R&D) approach grounded in the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research team meticulously crafted and refined the learning materials. Validation of the developed products involved rigorous scrutiny by a diverse panel of experts, including media specialists, materials experts, pedagogical experts, linguists, educators, and students. This comprehensive validation process integrated both qualitative and quantitative analyses to ensure the robustness and efficacy of the educational resources. Evaluation of the products yielded promising results, with expert validators assigning an overall score of 85, denoting a